2018
DOI: 10.1101/455014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wolbachia pipientisoccurs inAedes aegyptipopulations in New Mexico and Florida, USA

Abstract: The mosquitoes Aedes aegypti (L.) and Ae. albopictus Skuse are the major vectors of dengue, Zika, yellow fever and chikungunya viruses worldwide. Wolbachia, an endosymbiotic bacterium present in many insects, is being utilized in novel vector control strategies to manipulate mosquito life history and vector competence to curb virus transmission. Earlier studies have found that Wolbachia is commonly detected in Ae. albopictus but rarely detected in Ae. aegypti. In this study, we used a two-step PCR assay to det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 41 publications
2
18
1
2
Order By: Relevance
“…Through these analyses, we demonstrate conclusively that the LC population does not harbor Wolbachia. These results conflict with those from the original study (Kulkarni et al, 2019) and more recent tests by the authors…”
Section: Te S Ting a Putatively Wolbach Ia-infec Ted L Abor Atory Pcontrasting
confidence: 98%
See 4 more Smart Citations
“…Through these analyses, we demonstrate conclusively that the LC population does not harbor Wolbachia. These results conflict with those from the original study (Kulkarni et al, 2019) and more recent tests by the authors…”
Section: Te S Ting a Putatively Wolbach Ia-infec Ted L Abor Atory Pcontrasting
confidence: 98%
“…These studies report variable infection frequencies in populations and identify infections from several Wolbachia supergroups. Most studies found that the infections detected were closely related to or identical to the wAlbB infection that occurs natively in Aedes albopictus (Balaji et al, 2019;Carvajal et al, 2019;Coon et al, 2016;Kulkarni et al, 2019), while other studies also detected Wolbachia from supergroups that do not normally occur within Diptera (Carvajal et al, 2019;Thongsripong et al, 2018). Most evidence is limited to molecular detection, and not all studies claim to have discovered an active infection.…”
Section: De Tec Ti On S Of Wolbach Ia In a Ed E S Aegyptimentioning
confidence: 99%
See 3 more Smart Citations